1992
DOI: 10.1073/pnas.89.6.2504
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of a member of the S100 gene family in mammary carcinoma cells and reexpression by azadeoxycytidine treatment.

Abstract: A cDNA clone, designated CaN19 (originally called clone 19), isolated by subtractive hybridization, contains sequences that are preferentially expressed in normal mammary epithelial cells but not in breast tumor cells. Comparison of its deduced amino acid sequence with sequences in the GenBank data base revealed similarity with the S100 protein family, a group of small Ca(2+)-binding modulator proteins involved in cell cycle progression and cell differentiation. CaN19 expression is down-regulated in normal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 44 publications
6
118
0
1
Order By: Relevance
“…It is widely thought to be a tumour suppressor (Lee et al, 1992;Wicki et al, 1997;Nagy et al, 2001). However, S100A2 is strongly expressed in many tumours (Villaret et al, 2000;Hough et al, 2001;El-Rifai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely thought to be a tumour suppressor (Lee et al, 1992;Wicki et al, 1997;Nagy et al, 2001). However, S100A2 is strongly expressed in many tumours (Villaret et al, 2000;Hough et al, 2001;El-Rifai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These four proteins were subjected to ingel tryptic digestions. The MALDI-TOF MS analysis and peptide mass mapping of the tryptic digests subsequently identified the protein spots 1 and 2 as annexin II (Figure 2a, right panel), spot 3 as annexin I (Figure 2a, left panel), and spot 4 as S100A2, a calciumbinding protein (Lee et al, 1992). To confirm the peptide mass mapping results, we picked one of the peptide peaks for each protein obtained from MALDI-TOF MS (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Different from annexin II, the loss of annexin 7 expression appears to be because of loss of heterozygosity, thus indicative of gene mutations (Srivastava et al, 2001). It is of interest to note that S100A2, which, like p11 or S100A10, belongs to the S100 family of proteins, is also reduced in LNCaP cells (protein spot 4 in Figure 1b, panel d), as observed in breast cancer cells (Lee et al, 1992) and recently reported by others in prostate cancer cells (Gupta et al, 2002). Another S100 protein, S100A4, is also reduced in prostate cancers (Gupta et al, 2002).…”
Section: Annexin II Inhibits Migration Of Prostate Cancer Cellsmentioning
confidence: 95%
“…S100A2 is preferentially expressed in normal mammary epithelial cells but is down-regulated in breast tumor cells (19,20) and in several other tumor types as well (17). Expression of S100A2 can be altered by the calcium ionophore A23187 (down-regulation) and by the demethylating agent 5-azacytosine (up-regulation) in cell culture (19). Investigations of the methylation status of the S100A2 promotor region in normal (HBL100) and tumorigenic (T47D) cell lines showed that S100A2 expression is suppressed by DNA methylation (21).…”
mentioning
confidence: 99%
“…The cDNA coding for S100A2 was found through subtractive hybridization between normal and tumor-derived human mammary epithelial cells in a search for novel tumor suppressor genes (18). S100A2 is preferentially expressed in normal mammary epithelial cells but is down-regulated in breast tumor cells (19,20) and in several other tumor types as well (17). Expression of S100A2 can be altered by the calcium ionophore A23187 (down-regulation) and by the demethylating agent 5-azacytosine (up-regulation) in cell culture (19).…”
mentioning
confidence: 99%